The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.15628/holos.2017.6318
|View full text |Cite
|
Sign up to set email alerts
|

DESENVOLVIMENTO E CARACTERIZAÇÃO DE FILMES À BASE DE AMIDO DE FEIJÃO MACÁÇAR (Vigna Unguiculata)

Abstract: Neste trabalho foi desenvolvido e caracterizado filmes biodegradáveis à base de amido de feijão macáçar, plastificado com glicerol e com a mistura glicerol e ácido acético glacial (HAc). Os filmes foram obtidos por casting empregando amido de feijão macáçar (3 g/100 g de solução filmogênica) e diferentes concentrações do plastificante glicerol (20 e 30 g/100 g de amido) e da mistura glicerol e ácido acético glacial, nas proporções de 20 g e 10 g/100 g de amido, respectivamente. Os filmes apresentaram boas cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
(11 reference statements)
0
1
1
3
Order By: Relevance
“…Norajit et al (2010) found thickness between 0.13 to 0.07 mm and moisture content between 29.64 to 23.90% in alginate films incorporated with ginseng extract. Costa et al (2017) obtained a thickness less than that of this study between 0.09 to 0.10 mm in films based on solid bean starch with different amounts of glycerol and low solubility between 11.43 to 21.51%.…”
Section: Discussioncontrasting
confidence: 72%
“…Norajit et al (2010) found thickness between 0.13 to 0.07 mm and moisture content between 29.64 to 23.90% in alginate films incorporated with ginseng extract. Costa et al (2017) obtained a thickness less than that of this study between 0.09 to 0.10 mm in films based on solid bean starch with different amounts of glycerol and low solubility between 11.43 to 21.51%.…”
Section: Discussioncontrasting
confidence: 72%
“…Oliveira et al (2021) detected an average moisture content of 16.75% in the pectin-based film of yellow mombin (Spondias mombin L.). Costa et al (2017) formulated starch films from (Vigna unguiculata (L) Walp) with moisture contents Brazilian Applied Science Review, Curitiba, v.5, n.6, p. 2160-2175 nov./dez. 2021 between 14.45 and 26.50%.…”
Section: Resultsmentioning
confidence: 99%
“…O teor de umidade foi de 8,45%, e cinzas de 0,056% para o biofilme de C. lanatus Tabela 1. Costa et al (2017) [16], encontraram para biofilmes de amido do feijão macáçar, teores de umidade entre 14,45 a 26,50%. Já Dantas et al (2015) [17], avaliaram diferentes formulações de biofilmes, incorporados com polpas de frutas onde encontraram teor de umidade entre 10,93 a 19,69%.…”
Section: Resultsunclassified